Predicting Quality of Life among Mothers in an Online Health Community for Children with Type 1 Diabetes - Ju-Yeon Uhm; Myoung Soo Kim (MDPI AG, 2020)
Quality of life of parents of children with chronic disease is important for disease self-management. This study aimed to identify predictors of quality of life among mothers of children with type 1 diabetes. A cross-sectional study was conducted. A total of 208 mothers of children with type 1 diabetes were recruited from an online health community. Online health community collective empowerment and social support, diabetes self-efficacy, diabetes-related burden, and quality of life were measured. A multiple regression analysis was conducted to determine predictive factors for quality of life. Multiple regression analysis showed that diabetes-related burden and the child's age were predictors of quality of life, and total variance explained by the model was 64.1% using two factors. In mothers of younger children, it is important to reduce the diabetes-related burden. Factors that increase the diabetes-related burden should be identified, and strategies to reduce the diabetes-related burden must be established.